The Mystic Communities of William Blake and W. B. Yeats: Shared Spiritual Influences and Legacies - Marley, Jodie Lorna (2023)
Both William Blake’s and W. B. Yeats’ work is indebted to and driven by their spiritual convictions. Their engagement with the mystic and the esoteric within their social circles is mirrored across time. My thesis aims to make the case that the sources of these authors’ mysticisms, and their engagement with mystic spirituality in a community context impacted both Blake’s, and Yeats’ critical and cultural reception. My thesis presents the first extended literary discussion of both Dorothy Gott and Joanna Southcott’s work in comparison to Blake’s, including the first analysis of Blake’s Notebook fragment on Southcott, ‘On the Virginity of the Virgin Mary & Johanna Southcott’. I examine Blake in connection with Gott in my first chapter and Southcott in my second to argue the importance of women’s prophecy on Blake’s work, and how women’s prophecy is one of his major mystic influences. In my first chapter, I attempt to broaden the scope of Blake criticism on his women characters by arguing that women in childcare roles are spiritual teachers: Blake criticism, as I will explain in that chapter, often neglects women who aren’t young and /or sexualised. My first two chapters explore Blake’s neglected spiritual influences as well as his biblical and esoteric influences, with the aim of presenting a broader portrait of Blake’s spirituality and contextualising Blake’s reception as a ‘mystic’ by Yeats’ circle. My third chapter examines Yeats’ and Edwin J. Ellis’ three volume book of Blake criticism, biography, and edited poetry reproductions, The Works of William Blake Poetic, Symbolic, and Critical (1893). I argue for its significance both to Blake studies as a predecessor of S. Foster Damon, Kathleen Raine’s, and Kevin Fischer’s work which connects Blake to esoteric and mystic traditions. I also argue for The Works of William Blake as a predecessor to Yeats’ own A Vision, in which Yeats attempted to outline his own mystic system, and from which he later borrowed symbolism for his poetry. I demonstrate how Yeats’ 1890s literary criticism in article and review form contributed to Blake’s reception as a mystic, and how this created reputation of Blake allowed him to position himself and his circle as inheritors of Blake’s mystic legacy. My third chapter explores Yeats’ spirituality alongside that of George William Russell’s and Fiona Macleod’s/William Sharp’s. The fourth chapter considers the power of George Yeats’ and Iseult Gonne’s influence on Yeats’ archetype of the mystic, combined with Blake’s, Russell’s, and Macleod’s. I offer a close reading of a number of texts by Yeats, Russell, and Macleod, as well as George Yeats’ contributions to A Vision, in order to show how Yeats’ contemporaries influenced him, rather than vice versa. My third chapter focuses on works from the fruitful and formative 1890s period when Yeats, Russell, and Macleod were most deeply involved in spiritual and esoteric communities such as the Hermetic Order of the Golden Dawn (Yeats) and the Theosophical Society (Russell). My fourth chapter considers the period from 1906 to the publication history of A Vision up to 1925. I read Russell’s The Candle of Vision (1918) alongside Per Amica Silentia Lunae (1918) and A Vision in order to argue that Blake’s influence on two writers from the same circle and with similar interests produced very different results. My fourth chapter builds on the discussion of gender and the spiritual in chapters one and two. It offers an extended consideration of gender’s influence on mysticism in A Vision and explores how George Yeats and Gonne shaped the female examples of mysticism in this text. My thesis concludes that mysticism in the works of Blake and Yeats was transmitted through their communities, and that their spiritual work formed through collective, rather than individual, influences.